FACTORS ASSOCIATED WITH THE READINESS OF PATIENTS WITH HEART FAILURE TO BE DISCHARGED FROM A CARDIAC HOSPITAL - Григорець, Діана; Плеш, Ігор (SWorldJournal, 2024)
The article analyzes the factors that influence the readiness for discharge of patients with heart failure (HF) II-A and II-B stages according to Vasylenko-Stazhesko and II-IV functional classes according to NIHA, aged 30-85 years of the general cardiolog